Quality Analysis Of Used Cooking Oil Refining Results With Bioadsorbent Composition Of Palm Fiber Waste And Bleaching Earth - Muhammad Indra Darmawan; Adzani Ghani Ilmannafian; Mariatul Kiptiah; Khatimatul Husna (Agroindustrial Technology Journal, 2024)
Used cooking oil is oil resulting from repeated frying that can cause various diseases and pollute the environment. Therefore, as waste, it is necessary to make efforts to utilize used cooking oil waste, one of which is through regeneration using bioadsorbents of palm fiber waste and bleaching earth. The purpose of this study was to analyze the quality of bioadsorbents from palm fiber waste and analyze the quality of cooking oil refining results with palm fiber waste bioadsorbents, and bleaching the earth. The research method carried out is the manufacture of bioadsroben from palm fiber waste, oil refining using palm fiber waste bioadsorbent and bleaching earth with variations F1 (0%: 100%), F2 (25%: 75%), F3 (50%: 50%), F4 (75%: 25%), and F5 (100%: 0%), then analyzed the test results. The results showed that the quality of this bioadsorbent met the SNI 06-3730-1995 standard in the parameters of moisture content, ash content, pure activated carbon, part lost at 950 °C heating, and iodine absorbency parameters. The best results of used cooking oil permeated with palm fiber bioadsorbent and bleaching earth are at50% palm fiber bioadsorbent and 50% bleaching earth, which has decreased the value of water content, free fatty acids, acid numbers, and peroxide numbers even though it is still not in accordance with SNI-3741: 2013 and SNI-7709: 2019.